PENINGKATAN HASIL BELAJAR SISWA KELAS IVB PEMBELAJARAN IPAS MELALUI MEDIA PUZZLE DI SDN PETERONGAN - Isbat Dzikril Anam; Ngurah Ayu Nyoman; Fine Reffiane (STKIP Subang, 2023)
This research is useful to improve the learning outcomes of students in class IVB learning ipas through puzzle media at SDN Peterongan. The research used a Classroom Action Research (PTK) design and was conducted over two cycles. This assessment shows that there is an increase in learning outcomes in each cycle. In the pre-cycle, the students who were complete were 8 students or the percentage of complete 33% while those who were not complete were 16 students or the percentage of incomplete 67%. In cycle I, the students who were complete were 16 students or a percentage of 67% while the students who were not complete were 8 students or a percentage of 33% incomplete. In cycle II, the students who were complete were 20 students or a percentage of 83% complete while the students who were not complete were 4 students or a percentage of 17% incomplete. It can be concluded that there is an increase in the learning outcomes of class IVB students learning ipas by using puzzle media.